(untitled) (Eurasian Journal of Ecology, 2018)
Recently, significant air pollution occurs due to various industries. In this regard, air pollution is one of the urgent problems. Today, issues related to air pollution go beyond the problems of an individual country, affecting the interests of the entire international community. Purpose of the work is to research of atmospheric air pollution by carbon dioxide in the Ust-Kamenogorsk, located in the Ertis River Basin. The article provides a brief comparative analysis of the daily threshold limit value (TLV) of sulfur dioxide in Kazakhstan and the quality criteria for atmospheric air in other countries. In Kazakhstan, the territory of the Ertis basin region is the most urbanized, since the air atmosphere in the East Kazakhstan is considered highly polluted with sulfur dioxide, in which the main large industrial center and enterprises of different directions are concentrated. In this regard, the article was devoted to the pollution of atmospheric air in Ust-Kamenogorsk in the Ertis River basin by harmful substances, including sulfur dioxide, based on data from various sources. The practical significance of this research work is to identify the distribution of sulfur dioxide in Kazakhstan in comparison with other countries, detection of sources of pollution in the analyzed area, determination of the negative impact on the environment and development of recommendations. In the research, methods of system analysis, synthesis, ecology-statistical, comparative and cartographic methods were applied. The main results were made on the basis of samples of research stations and reports of the Center for Environmental Safety. Taking into account the main causes of pollution, the consequences of damage to the environment, including health effects, were considered. In conclusion, recommendations were made to reduce atmospheric air pollution in Ust-Kamenogorsk Key words: Ecological crisis, pollution, industrial enterprise, sulfur dioxide, maximum permissible concentrations (MPC)